Hygrothermal and mechanical characterisation of novel hemp shiv based thermal insulation composites. (10th July 2019) - Hussain, Atif; Calabria-Holley, Juliana; Lawrence, Mike; Jiang, Yunhong
Highlights: Development of novel hemp shiv based composites with low thermal conductivity of 0.05 W/mK. Enhanced vapour permeability and excellent moisture buffering value up to 3.6 g/m 2 RH. Pre-treatment of hemp shiv leads to high water resistance reducing water absorption by 123%. The composites have low density (175–240 kg/m 3 ) and show good mechanical performance. Abstract: This study focuses on the development of advanced water resistant bio-based composites with enhanced hygrothermal performance for building applications. The highly porous structure of hemp shiv is responsible for low thermal conductivity and allows the material to adapt to varying humidity conditions providing comfortable indoor environment. However, the pore network and the hydrophilic nature of hemp shiv affects the compatibility and durability of the material in presence of excess moisture conditions. In this work, novel hemp shiv composites were prepared in a starch based or silica based matrix and characterised for their hygroscopic, thermal and mechanical properties. The hemp shiv based composites were resistant to water yet permeable to vapour and showed excellent moisture buffering capacity when compared to conventional hemp-lime composites. The composites prepared were light weight with low thermal conductivity values of 0.051–0.058 W/mK and showed good mechanical performance. Hemp shiv composites with superior hygrothermal characteristics have immense potential as robust thermal insulation building materials.